2009
DOI: 10.1111/j.1365-2133.2009.09608.x
|View full text |Cite
|
Sign up to set email alerts
|

Secreted subtilisin Sub3 from Microsporum canis is required for adherence to but not for invasion of the epidermis

Abstract: RNA interference is a useful tool to evaluate pathogenic mechanisms of M. canis. For the first time, a role in pathogenicity could be attributed to a protease of a dermatophyte, namely Sub3 from M. canis, which is required for adherence to but not for invasion of the epidermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 40 publications
(55 reference statements)
2
53
0
Order By: Relevance
“…In line with this assumption, previous studies of reconstituted human epithelia infected with C. albi- cans revealed that supplementation of the model with polymorphonuclear leukocytes strongly impaired tissue invasion by this pathogenic yeast (22). In the past, various in vitro models using reconstituted epidermis or skin explants have been established and were also proven successful for the analysis of dermatophytosis (1,2,5,7,19,20,24,26). Nevertheless, the commercially available RHE model, which was employed in the present study for the analysis of A. benhamiae mutants, may further advance the research of dermatophytosis and the identification of basic virulence attributes of dermatophytes.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In line with this assumption, previous studies of reconstituted human epithelia infected with C. albi- cans revealed that supplementation of the model with polymorphonuclear leukocytes strongly impaired tissue invasion by this pathogenic yeast (22). In the past, various in vitro models using reconstituted epidermis or skin explants have been established and were also proven successful for the analysis of dermatophytosis (1,2,5,7,19,20,24,26). Nevertheless, the commercially available RHE model, which was employed in the present study for the analysis of A. benhamiae mutants, may further advance the research of dermatophytosis and the identification of basic virulence attributes of dermatophytes.…”
Section: Discussionmentioning
confidence: 70%
“…Animal infection was monitored twice weekly for 7 weeks by two independent examiners using clinical criteria, as previously described (1,3). The examiners remained the same for the duration of the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model has been useful for zoophiles [33, 5254] but does not provide an accurate infection model for most anthropophilic species [4]. A murine model has been useful for studying the immune response to dermatophytes [55, 56], but again the mice only develop disease in response to infection by zoophiles.…”
Section: Testing the Role Of Putative Virulence Factorsmentioning
confidence: 99%
“…In cats, several attempts have been made to develop vaccines using characterized antigens from M. canis. The protective efficacy of a crude exo-antigen and two recombinant proteases, the subtilisin rSub3, a fungal endopeptidase involved in adherence of M. canis to human and animal epidermis (Baldo et al, 2010;Bagut et al, 2012), and the metalloprotease rMep3 have been tested in experimentally induced M. canis infections in guinea pig with inconclusive results (Descamps et al, 2003;Vermout et al, 2004). The development of safe and effective vaccines requires the use of both appropriate antigens and adjuvants.…”
mentioning
confidence: 99%